Use of Vegetable and Fruit Waste To Make Environmentally Friendly Liquid Fertilizer In The Growth of The Indonesian Community of Pinang - I G. Ayu Arwati; Wiwit Suprihatiningsih; Sagir Alva; Muhammad Fitri; Imam Hidayat; Sawarni Hasibuan (International Journal Of Community Service, 2024)
This community service partner is the Non-Governmental Organization (NGO) PERMAI in Penang. PERMAI members are generally Indonesian workers who work in Penang, some of whom work as home-based food traders. Around where he lives, traders produce waste, including organic waste from cooking activities and leftovers from selling vegetables and fruit. This organic waste rots easily if left alone, causing an unpleasant odor in the surrounding area and causing a smelly and unhealthy environment. One way to handle organic waste, especially rotten fruit and vegetables produced from household or restaurant waste, is by making liquid fertilizer. The implementation method used is two stages, namely: 1) preparation stage; production originating from appropriate technological equipment activities for making liquid fertilizer, discussions and sharing with team members, and 2) the stage of implementing community service at partner locations, distributing questionnaires before and after the exposure. The expected target in this community service activity is to increase the knowledge of the Indonesian working community in Pulau Pinang regarding how to make and the benefits of liquid fertilizer which can be made from everyday household vegetable and fruit waste.